IVR: student management and reverse charge call services / Shahirwan Md Lazi - Md Lazi, Shahirwan (2007)
This thesis present a software development of a system, build as a medium of core activity for the respondent answers each question by pressing the keys on the telephone keypad, and responses are entered automatically in a database. System admin can also make editing on database. How do the system work ?. This system will allow student to check their status of registration, previous exam result, check summon and services for reverse charge call to their hometown. Student needs to use the telephone that has been allocated at their college or faculty. As simple as the student just key in their student id and select which services their want. This interactive voice response(IVR) system is built with hardware Intel Dialogic Card is used in this project and the software is developed using Computer Telephony Application Development Environment (CT ADE) for main software and Microsoft SQL Server 2000 for student database. All phone activities are controlled by PABX for the interface using telephone for user interaction.